2013
DOI: 10.1080/01635581.2013.756528
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tamoxifen with Edible Seaweed (Eucheuma cottonii L.) Extract in Suppressing Breast Tumor

Abstract: The tropical edible red seaweed (Eucheuma cottonii L.) is rich in nutrients and polyphenolic compounds that may suppress cancer through its antioxidant and antiproliferative properties. The study reports on rat mammary tumor suppression and tissue antioxidant status modulation by E. cottonii ethanol extract (ECE). The effect of orally administered ECE (100 mg/kg body-weight) was compared with that of tamoxifen (10 mg/kg body-weight). Rat was induced to develop mammary tumor with subcutaneous injection of LA-7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 57 publications
2
16
0
2
Order By: Relevance
“…EC and seaweeds such as S. binderi, C. lentillifera, and C. racemosa are known to be potent sources of antioxidants [3], [11], [15]- [17]. Furthermore, EC consumption enhances gluthionine (GSH) production [18] and exhibited better antihyperlipaemic and in vivo antioxidant effects as compared to C. lentillifera and S. polycystum seaweeds [7].…”
Section: Discussionmentioning
confidence: 99%
“…EC and seaweeds such as S. binderi, C. lentillifera, and C. racemosa are known to be potent sources of antioxidants [3], [11], [15]- [17]. Furthermore, EC consumption enhances gluthionine (GSH) production [18] and exhibited better antihyperlipaemic and in vivo antioxidant effects as compared to C. lentillifera and S. polycystum seaweeds [7].…”
Section: Discussionmentioning
confidence: 99%
“…High Urokinasetype plasminogen activator receptor (uPAR) expression predicts for more aggressive disease in several cancer types [167], dietary seaweed may help lowering breast cancer incidence by diminishing levels of uPAR [168]. The tropical edible red seaweed Eucheuma cottonii L. ( Figure 10) is rich in polyphenols that exhibited strong anticancer effect with enzyme modulating properties [169]. Jazzara et al [170] concluded that λ-carrageenan (sulfated galactans found in certain red seaweeds) could be a promising bioactive polymer, showed a remarkable inhibitory effect on MDA-MB-231(triple negative breast cancer cell line) cell migration [171].…”
Section: Cancer Prevention and Tumor Controlmentioning
confidence: 99%
“…High Urokinasetype plasminogen activator receptor (uPAR) expression predicts for more aggressive disease in several cancer types [377], dietary seaweed may help lowering breast cancer incidence by diminishing levels of uPAR [378]. The tropical edible red seaweed Eucheuma cottonii L. ( Figure 7d) is rich in polyphenols that exhibited strong anticancer effect with enzyme modulating properties [379]. Jazzara, et al [380] concluded that λ-carrageenan ( Figure 6f) (sulfated galactans found in certain red seaweeds) could be a promising bioactive polymer, showed a remarkable inhibitory effect on MDA-MB-231(triple negative breast cancer cell line) cell migration [381].…”
Section: Camptotheca Acuminate (Xǐ Shù or Happy Tree) Leavesmentioning
confidence: 99%